Endoscopic anatomical study on anterior communicating artery aneurysm surgery by endonasal transphenoidal approach. Issue 1 (December 2016) - Ma, Junwei; Wang, Zhimin; Zhang, Niankai; Li, Shengshan; Jiang, Dongyi; Chen, Hanchun
Abstract Background Endonasal transphenoidal approach by neuroendoscopy has its own advantage, such as direct access, invasive, better visualization of the anterior communicating artery aneurysm and so on. The study is to provide anatomical knowledge for anterior communicating artery aneurysm surgery by endonasal transphenoidal approach with neuroendoscopy. Materials Take 10 skull base specimens, observe and measure the anatomical structures around anterior communicating artery. Take 10 cadaveric heads, simulate the anterior communicating artery aneurysm surgery with neuroendoscopy by endonasal transphenoidal approach. Find the natural opening of sphenoid sinus, then open the skull base, expand bone window in anterior skull base. After that, cut off the dura, find the optic nerve, optic chiasm, cisterna lamina terminalis, anterior cerebral artery, a portion of frontal lobe, anterior communicating artery complex and its important branches, such as heubner artery, hypothalamic artery, orbitofrontal artery and so on. Lift up anterior communicating artery complex and seperate arachnoid in cisterna lamina terminalis, the lamina terminalis is exposed. Block bilateral A1 of anterior cerebral artery with aneurysm clip, the anterior communicating artery complex and its important branches are in view, so we can clip anterior communicating artery aneurysm safely. Results Anterior communicating artery aneurysm surgery can be finished with neuroendoscopy by endonasal transphenoidal approach. The vital structures can be clearly observed with neuroendoscopy. The rhombus anatomic region formed by bilateral olfactory nerve and optic nerve is a safe surgical area. According to the calculation, the safe surgical area is about 161.48 ± 12.78 mm2 . Measure the distance between the important anatomic structures in the rhombus anatomic region. By means of SPSS 17 Statistical analysis software, the measuring distance is expressed with (x ± S)mm. Conclusion The anterior communicating aneurysm surgery by endonasal transphenoidal approach with neuroendoscopy has its own advantage, such as direct access, minimally invasive, less bleeding, light pain, quick recovery, better visualization of the anterior communicating artery aneurysm and so on. This operation approach needs further study and exploration to clinical application, in order to become a mature approach of anterior communicating artery aneurysm surgery.